Pengaruh Tingkat Inflasi, Solvabilitas dan Profitabilitas Terhadap Harga Saham Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Salsabila, Diva Azka; Amin, Moh.; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This have a look at become performed to investigate the effect of the solvency ratio of inflation and profitability on stock expenses Case studies of producing corporations within the consumer items enterprise subsector listed at the Indonesian inventory trade in 2018-2020. The pattern used in this examine is a producing agency inside the patron items industry subsector that is indexed at the Indonesian stock change (IDX) for the duration 2018-2020. primarily based at the effects of the checking out inside the previous chapter, it could be concluded that the simultaneous test effects display that profitability and solvency have a significant impact on the proportion prices of manufacturing agencies inside the client goods enterprise subsector listed at the Indonesian inventory trade in 2018-2020. Partial check outcomes show that inflation does now not have a massive effect on the stock fees of producing corporations inside the customer goods enterprise subsector indexed at the Indonesian stock change in 2018-2020. Partial check effects display that solvency and profitability have a fantastic and massive effect on the proportion expenses of manufacturing companies inside the customer goods industry subsector listed at the Indonesian stock alternate in 2018-2020.Keywords: Inflation, profitability, solvency, share price.